Essentials of fuzzy modeling and control - Yager, Ronald R., 1941- (Wiley, 1994)
At last, here is a thorough introduction that offers complete coverage of all relevant theory and applications to the rapidly evolving field of fuzzy logic. While most other books on the subject tend to be loose collections of papers reporting on the state of this or that fuzzy area, Essentials of Fuzzy Modeling and Control follows a logical, pedagogically consistent format designed to fully acquaint readers with the entire range of fuzzy concepts, tools, and modeling techniques. While it is an excellent general introduction for students, the authors' ultimate goal is to give researchers an opportunity to acquire everything they need to build the kinds of fuzzy rule-based models used in the development of the controllers now being constructed for the next generation of intelligent systems.